Environmental Kuznets curve and financial development in Pakistan. (February 2016) - Javid, Muhammad; Sharif, Fatima
Abstract: In this study, we analyzed the effects of financial development, per capita real income, the square of per capita real income, per capita energy consumption and openness on per capita CO2 emissions for Pakistan during 1972–2013. The bound F -test for cointegration yielded evidence of a long-term relationship among these variables. The results confirm the existence of an environmental Kuznets curve in Pakistan for both the short and long term. This finding indicates that at the initial stage of development, the level of CO2 increases with income, and after some threshold level of income, this relationship may change from positive to negative as more efficient infrastructure and energy-efficient technology are implemented during the development process of the country. The findings of this study also reveal a significantly positive sign for the coefficient of financial development, suggesting that financial development has occurred at the expense of environmental quality. The results further indicate that the key contributing factors to carbon emissions in Pakistan are income, energy consumption and financial development. In addition, the openness variable has no significant influence on carbon emission in either the short or long term.